2023
DOI: 10.18632/aging.204564
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of apoptosis through AKT-mTOR pathway in ovarian cancer and renal cancer

Abstract: Objective: Ovarian cancer and renal cancer are malignant tumors; however, the relationship between TTK Protein Kinase (TTK), AKT-mTOR pathway and ovarian cancer, renal cancer remains unclear. Methods: Download GSE36668 and GSE69428 from Gene Expression Omnibus (GEO) database. Weighted gene co-expression network analysis (WGCNA) was performed. Created protein-protein interaction (PPI) network. Used Gene Ontology analysis (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) for functional enrichment analysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In lung adenocarcinoma, upregulated STXBP1 expression correlates with poor prognosis [76]. Threonine and tyrosine kinase (TTK), alternatively referred to as unipolar spindle 1 (Mps1), acts as a spindle assembly checkpoint, guaranteeing the precise segregation of chromosomes into daughter cells [77]. Apart from the testes and placenta, TTK is rarely detected in normal tissues [78].…”
Section: Discussionmentioning
confidence: 99%
“…In lung adenocarcinoma, upregulated STXBP1 expression correlates with poor prognosis [76]. Threonine and tyrosine kinase (TTK), alternatively referred to as unipolar spindle 1 (Mps1), acts as a spindle assembly checkpoint, guaranteeing the precise segregation of chromosomes into daughter cells [77]. Apart from the testes and placenta, TTK is rarely detected in normal tissues [78].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we first reported that ANXA2 interacts with TTK and acts as a molecule upstream of TTK, regulating ESCC cell growth and metastasis. Chen et al reported that TTK inhibits apoptosis through the Akt/mTOR pathway in ovarian cancer [ 49 ]. Besides, TTK was found to regulate tumor proliferation in gastric cancer, colon cancer and HCC [ 50 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Activation of AKT is the most common signaling mechanism involved in OC cell survival, growth, and proliferation [10][11][12]. Previous studies have demonstrated that FBXL18 promotes glioblas- toma cell proliferation via promoting K63-linked ubiquitination to activate AKT signaling in human glioma cancer [13].…”
Section: Fbxl18 Is Required For Oc Cell Proliferation and Migration V...mentioning
confidence: 99%